Epistemologi, Ontologi, Dan Aksiologi Ilmu Ekonomi Islam Dalam Kerangka Falsafah Ekonomi Syariah - Fitri Bahreni; Iska, Syukri; Hidayati, Azifah; Marlion, Fandi Ahmad (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Islamic economics emerges as an alternative paradigm that offers a value-based philosophical foundation through the integration of epistemology, ontology, and axiology within the framework of Islamic economic philosophy. This study aims to conceptually examine the epistemological, ontological, and axiological dimensions of Islamic economics and their integration as the foundation for the development of Islamic economic thought. Employing a qualitative descriptive approach with a library research method, the data were derived from the Qur’an, Hadith, and contemporary academic literature relevant to Islamic economics and the philosophy of science. The findings indicate that the epistemology of Islamic economics is integrative, positioning revelation as the primary source of knowledge that guides reason and empirical inquiry; its ontology views economic reality as a holistic system grounded in the principle of tawhid, in which humans function as both servants (‘abd) and vicegerents (khalifah); while its axiology is oriented toward the realization of falah through the values of justice, balance, trust, and public welfare. The integration of these three dimensions within Islamic economic philosophy affirms that Islamic economics is not merely a technical or pragmatic alternative to conventional economics, but a value-driven and ethical discipline aimed at achieving holistic and sustainable human well-being.